2012
DOI: 10.1073/pnas.0912951109
|View full text |Cite
|
Sign up to set email alerts
|

Paths of convergence for agriculture, health, and wealth

Abstract: This special feature calls for forward thinking around paths of convergence for agriculture, health, and wealth. Such convergence aims for a richer integration of smallholder farmers into national and global agricultural and food systems, health systems, value chains, and markets. The articles identify analytical innovation, where disciplines intersect, and cross-sectoral action where single, linear, and siloed approaches have traditionally dominated. The issues addressed are framed by three main themes: ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
86
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 39 publications
1
86
0
1
Order By: Relevance
“…Biodiversity associated with dietary diversity of children, but the relationship was moderated by the socioeconomic status of the household. This finding is consistent with other studies that have shown a strong positive relationship between biodiversity in agricultural production and improved diversified diets [37–40]. The links between biodiversity and dietary diversity at the household or individual levels, however, remain inconclusive.…”
Section: Discussionsupporting
confidence: 91%
“…Biodiversity associated with dietary diversity of children, but the relationship was moderated by the socioeconomic status of the household. This finding is consistent with other studies that have shown a strong positive relationship between biodiversity in agricultural production and improved diversified diets [37–40]. The links between biodiversity and dietary diversity at the household or individual levels, however, remain inconclusive.…”
Section: Discussionsupporting
confidence: 91%
“…The boom in urbanization has resulted in a steep increase in demand for food, especially high value crops such as fruits, vegetables and other horticultural crops [4]. Food production is no longer seen simply as providing nutrition for a growing population but also as contributing to poverty reduction, better health outcomes and conservation of natural resources [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…12 Countries that have managed to improve nutritional status in these contexts have adopted an approach that targets the whole of society. 13 This approach requires a good understanding of the political economy of nutrition. Governments and other stakeholders in successful countries have built alliances, managed tensions, identifi ed win-win outcomes, established strong account ability mechanisms, and innovated in the mobilisation of resources for nutrition.…”
mentioning
confidence: 99%